The TEACHER METHODS IN BUILDING THE DISCIPLINE CHARACTER OF LEARNING THROUGH THE SCHOOL ENVIRONMENT AFTER THE PANDEMIC PERIOD IN PAUD NEGERI DEVELOPMENT 1, BENGKULU CITY - Dioba, Two Essy; Partikasari, Rika; Imran, Ranny Fitria (Early Childhood Research and Practice, 2023)
The purpose of this study was to 1) find out the methods used by teachers in building the character of learning discipline through the school environment after the pandemic at PAUD Negeri Pembina 1 Bengkulu City, 2) find out the supporting factors and inhibiting factors for teachers in building the character of learning discipline through the school environment after during the pandemic at PAUD Negeri Pembina 1 Bengkulu City. Qualitative research methods with a descriptive approach. Informants in this study were 2 people consisting of the Head of Pembina I Bengkulu Public PAUD and teachers. Data collection techniques used in this study were observation, interviews and documentation. Data analysis techniques Data analysis techniques from the Miles and Huberman concepts, the data analysis process is carried out interactively and continues continuously until it is complete so that the data is saturated. The results of the study show the methods used by teachers in building the character of learning discipline through the school environment in PAUD Negeri Pembina 1 Kota Bengkulu consists of exemplary methods, habituation, advice and attention or supervision of existing rules at school and attitudes of daily life such as coming to school on time, queuing in washing hands, cleaning up toys, and so on. Supporting factors and inhibiting factors for teachers in building the character of learning discipline through the school environment after the pandemic at PAUD Negeri Pembina 1 Bengkulu City are divided into internal and external factors. Supporting factors can be seen from the awareness of the students themselves while external inhibiting factors can be seen from parents and environmental factors